The role of gesture in speech interaction and in language development - Pavelin, Bogdanka (Array, 1999)
Sound and movement constitute the global speech act in the face-to-face interaction. Posturomimogestual manifestation and pauses, are together with the verboacoustic activity, esential components of the global speech activity in the given situation. The term of posturomimogestuality or shorter PMG, is chosen in order to take into account the importance of the global body movement i. e. not only hand movements (often referred to by the term of gesture), but also the body movement in general, as well as posture, spatial organization, facial expressions, eye contacts, touches. Our poster presents different functions of PMG manifestations in the global langugage expression as well as the order in which these functions appear and develop in harmony with the development of the linguistic aspect in child's speech.